Pregnancy outcome in patients exposed to direct oral anticoagulants - and the challenge of event reporting - Beyer-Westendorf, Jan; Michalski, Franziska; Tittl, Luise; Middeldorp, Saskia; Cohen, Hannah; Kadir, Rezan Abdul; Arachchillage, Deepa Jayakody; Arya, Roopen; Ay, Cihan; Marten, Sandra (Thrombosis and Haemostasis, 2016)
Today, direct oral anticoagulants (DOAC) are widely used alternatives to Vitamin-K antagonists (VKA). Women of reproductive age may become pregnant during anticoagulation and, while VKA carry an embryotoxic potential, the risk of DOAC embryopathy is unknown. As a result, some patients elect to terminate pregnancy for fear of DOAC embryotoxicity. To assess the risk of DOAC embryopathy, we reviewed cases of DOAC exposure in pregnancy collected from physicians, literature and pharmacovigilance systems of drug authorities and manufacturers. A total of 357 reports including duplicates were available from which 233 unique cases could be identified. Information on pregnancy outcome was available in only 137/233 cases (58.8 %): 67 live births (48.9 %); 31 miscarriages (22.6 %); 39 elective pregnancy terminations (28.5 %). In 93 cases (39.9 %) no outcome data were available (including 3 cases of ongoing pregnancy). Of the 137 pregnancies with reported outcomes, seven showed abnormalities (5.1 %) of which three (2.2 %) could potentially be interpreted as embryopathy: live birth with facial dysmorphism; miscarriage in week 10 with limb abnormality; elective pregnancy termination due to a foetal cardiac defect in a woman who had to terminate a previous pregnancy due to Fallot tetralogy. Within its limitations (small numbers, incomplete outcome data) our results do not indicate that DOAC exposure in pregnancy carries a high risk of embryopathy or that DOAC exposure per se should be used to direct patient counselling towards pregnancy termination. Pregnancy outcome data are inconsistently captured in pharmacovigilance databases indicating the strong need for a more robust system of reporting.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Pregnancy; direct oral anticoagulants; outcome